2021
DOI: 10.1542/peds.2020-049536
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Fatalities Associated With Over-the-Counter Cough and Cold Medications

Abstract: BACKGROUND AND OBJECTIVES: In 2008, over-the-counter cough and cold medications (CCMs) underwent labeling changes in response to safety concerns, including fatalities, reported in children exposed to CCMs. The objective of this study is to describe fatalities associated with exposures to CCMs in children <12 years old that were detected by a safety surveillance system from 2008 to 2016.METHODS: Fatalities in children <12 years old that occurred between 2008 and 2016 associated with oral exposure to one or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…In comparison, an observational study reported 40 out of 180 fatalities related to children < 12 years old. The most prevalent cause of fatality was diphenhydramine ingestion [ 19 ]. Furthermore, CCM-related fatalities, primarily among young children, were given by a caregiver for non-medical purposes.…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In comparison, an observational study reported 40 out of 180 fatalities related to children < 12 years old. The most prevalent cause of fatality was diphenhydramine ingestion [ 19 ]. Furthermore, CCM-related fatalities, primarily among young children, were given by a caregiver for non-medical purposes.…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, CCM-related fatalities, primarily among young children, were given by a caregiver for non-medical purposes. Seven fatal cases were associated with intentional use of sedation [ 19 ]. One study reported that from 2008 to 2016, > 40% of CCM-associated fatalities occurred in children < 12 years old [ 12 , 19 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations